Conceptualising the public health role of actors operating outside of formal health systems: The case of social enterprise. (January 2017) - Roy, Michael J.; Baker, Rachel; Kerr, Susan
Abstract: This paper focuses on the role of actors that operate outside formal health systems, but nevertheless have a vital, if often under-recognised, role in supporting public health. The specific example used is the 'social enterprise', an organisation that seeks, through trading, to maximise social returns, rather than the distribution of profits to shareholders or owners. In this paper we advance empirical and theoretical understanding of the causal pathways at work in social enterprises, by considering them as a particularly complex form of public health 'intervention'. Data were generated through qualitative, in depth, semi-structured interviews and a focus group discussion, with a purposive, maximum variation sample of social enterprise practitioners (n = 13) in an urban setting in the west of Scotland. A method of analysis inspired by critical realism – Causation Coding – enabled the identification of a range of explanatory mechanisms and potential pathways of causation between engagement in social enterprise-led activity and various outcomes, which have been grouped into physical health, mental health and social determinants. The findings then informed the construction of an empirically-informed conceptual model to act as a platform upon which to develop a future research agenda. The results of this work are considered to not only encourage a broader and more imaginative consideration of what actually constitutes a public health intervention, but also reinforces arguments that actors within the Third Sector have an important role to play in addressing contemporary and future public health challenges. Highlights: Considers the health role of actors outside of formal health systems. Focuses upon the example of social enterprise. Presents empirically-informed conceptual model of causal pathways. Encourages a more imaginative consideration of what we think of as an 'intervention'.